Influences of mechanized tillage and sowing modes on soil physical properties, soybean yield and economic benefits in mollisols region of Northeast China - Chen, Haitao; Sun, Jian; Zhang, Yiming; Qiao, Jinyou (International Journal of Agricultural and Biological Engineering, 2024)
Appropriate mechanized straw returning and tillage sowing techniques were effective means to optimize soil physical properties and enhance agricultural productivity, as well as important measures for the conservation and restoration of mollisols region in Northeast China. Under the condition of full-scale maize straw returning, four mechanized tillage and sowing modes were set, including plough tillage and sowing (PTS), combined tillage and sowing (CTS), no-tillage and sowing (NTS), and no-tillage and sowing with straw mulching (NTSM). In 2020 and 2021, the study investigated the effects of different mechanized tillage and sowing modes on soil physical properties, soybean yield and economic benefits. The results showed that during the pod-setting and pod-filling period of soybean, the NTS and NTSM treatments exhibited better effects on deep soil insulation and shallow soil moisture retention, the soil physical structure of PTS and CTS treatments were relatively ideal. Compared with PTS and CTS treatments, NTS and NTSM treatments significantly increased soil gravimetric water content (SWC) by 2.35% to 7.98% in the 5-15 cm soil layer and increased soil temperature (ST) by 3.94% to 10.42% in the 25-35 cm soil layer (p<0.05), significantly increased soil bulk density (SBD) by 2.98% to 6.72% and significantly reduced soil total porosity (STP) by 3.88% to 6.53% in the 5-25 cm soil layer, and significantly reduced soil gas phase ratio by 8.26% to 6.27% at the 15-25 cm soil layers, which caused soil three-phase ratio (STPR) of PTS and CTS treatment in 15-25 cm soil layer were relatively ideal. The soybean yield of NTSM treatment in 2020 was not significantly different from PTS and CTS treatment (p>0.05), the soybean yield of NTSM treatment in 2021 significantly increased by 7.30% and 5.84% over PTS and CTS treatments, respectively. And the average annual profit per unit area of NTSM treatment increased by 12.84%, 12.41% and 8.57% compared with PTS, CTS and NTS treatments, respectively. Therefore, it was recommended to combine NTSM technique with PTS or CTS technique in a maize-soybean rotation system in mollisols region. The research results provided reference for the selection of appropriate mechanized tillage and sowing techniques in Northeast China’s mollisols region and had important guiding significance and practical value for the construction of rational plow layers and the implementation of conservation tillage. Keywords: mechanized tillage and sowing modes, full-scale straw returning, soil physical properties, soybean yield, economic benefits, mollisols conservation DOI: 10.25165/j.ijabe.20241703.8724 Citation: Chen H T, Sun J, Zhang Y M, Qiao J Y. Influences of mechanized tillage and sowing modes on soil physical properties, soybean yield and economic benefits in mollisols region of Northeast China. Int J Agric & Biol Eng, 2024; 17(3): 130-139.